EVALUASI FUNGSI VEGETASI DAN PENGARUHNYA TERHADAP KENYAMANAN TERMAL LANSKAP JALAN KOTA MALANG - Uran, Rofinus Seri; Alfian, Rizki; Soelistyari, Hesti Triana (Fakultas Pertanian, 2017)
Most of the streetscape in Malang are less concerned with the physical and social conditions of streetscape, pavement elements, and vegetation maintenance on the streetscape. streetscape plays an important role in building environmental, spatial, and visual characteristics in order to provide an urban identity, especially in Idjen Boulevard and Langsep Street in Malang City which has different character of different roads. This study aims to: 1) identify the pathway green vegetation of roads on New Boulevard and Langsep Street ; 2) analyze the thermal comfort of the road landscape in Idjen Boulevard and Langsep Street; 3) evaluate the comfort level in Idjen Boulevard and Langsep Street. The method used by the convenience index analysis is the THI approach. The THI values obtained were then analyzed using the standards of Laurie (1990). Field observations show the Idjen Boulivard has a value of THI 28.52 and Langsep Street has value of THI 27.60. THI value of both roads are beyond the THI comfort value of 21-27 Idjen Boulevard 31.01-31.54 ° C with humidity 56.19-57.74%, and Langsep Street 29.51-40.84 ° C with humidity 58.67-60.86%. This is influenced by the density of the tree canopy and the spacing of trees on the streetscape. The temperature of the air and humidity can be modified by selecting the appropriate shade vegetation species. To scale the road in the city, so it is necessary to use shade plants with plant canopy that has a root system that does not damage the road construction, branching plants are not easily broken and easy in maintenance. Sebagian besar lanskap jalan Kota Malang kurang memperhatikan kondisi fisik dan sosial lanskap jalan, elemen perkerasan, dan pemeliharaan vegetasi pada lanskap jalan. Lanskap jalan berperan penting dalam membangun karakter lingkungan, spasial, dan visual agar dapat memberikan suatu identitas perkotaan khususnya di Jalan Besar Idjen dan Jalan Raya Langsep di Kota Malang yang memiliki karakter jalan berbeda beda. Penelitian ini bertujuan untuk: 1) mengidentifikasi vegetasi jalur hijau lanskap jalan di Jalan Besar Idjen dan Jalan Raya Langsep, 2) menganalisis kenyamanan thermal lanskap jalan di Jalan Besar Idjen dan Jalan Raya Langsep, 3) mengevaluasi tingkat Kenyamanan di Jalan Besar Idjen dan Jalan Raya Langsep. Metode yang digunakan analisis indeks kenyamanan adalah pendekatan THI. Nilai THI yang didapat kemudian dianalisis menggunakan standar dari Laurie (1990). Pengamatan di lapangan menunjukkan Jalan Besar Idjen memiliki nilai THI 28,52 dan Jalan Raya Langsep nilai THI 27,60. Nilai THI kedua jalan tersebut berada diluar nilai kenyamanan THI yaitu 21-27. Jalan Besar Idjen 31,01-31,54°C dengan kelembaban 56,19-57,74%, dan Jalan Raya Langsep 29,51-40,84°C dengan kelembaban 58,67-60,86%. Hal ini dipengaruhi oleh kerapatan tajuk pohon dan jarak tanam pohon pada lanskap jalan. Suhu udaradan kelmbaban dapat dimodifikasi dengan memilih jenis vegetasi penaung yang sesuai. Untuk skala jalan di kota, sehingga perlu digunakan tanaman penaung dengan tajuk tanaman yang mempunyai system perakaran yang tidak merusak konstruksi jalan, percabangan tanaman tidak mudah patah dan mudah dalam pemeliharaannya.